Global Norms and Local Resistance: The Concentration of LGBTQ+ Groups in Three Southern Thai Border Provinces - Ikrom Ingding (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
In the three border provinces of Pattani, Yala, and Narathiwat in southern Thailand, where most of the population is Malay Muslim with strong religious and cultural beliefs, this study examines the dynamics of acceptance and rejection of international conventions regarding the rights of LGBTQ+ individuals. Despite Thailand's notable advancements in LGBTQ+ rights, including the enactment of the Equal Marriage Act in 2024, research indicates that the three border provinces of Southern Thailand face substantial obstacles in implementing this law because of stringent religious and cultural standards. To obtain some acceptance, LGBTQ+ groups in the area are employing adaptation techniques like social media use, creating support systems, and highlighting Islamic principles like